Women’s Rights in Divorce and Post-Divorce Maintenance: Perspectives from Islamic Family Law in Indonesia and Human Rights - Selvy Yuspitasari (Yayasan Cerdas Pedia Indonesia, 2026)
This research analyzes the fulfillment of women's post-divorce financial rights within Indonesia's Islamic family law, confronting classical fiqh dogmas with human rights principles and maqashid al-syariah. Despite progressive legal frameworks and Supreme Court guidelines, empirical data reveals a systemic failure in securing alimony, particularly during wife-initiated divorces. Utilizing a mixed-methods socio-legal approach, this study identifies patriarchal interpretations, procedural rigidities like verstek rulings, and the crucial absence of an authorized state executorial body as fundamental obstacles. The findings indicate that relying solely on judicial ex officio interventions remains insufficient without structural reforms. To eliminate post-divorce economic marginalization and achieve substantive gender justice, Indonesia urgently requires the establishment of an autonomous execution institution. This agency must be fully integrated with the national banking sector to enforce alimony compliance directly. Ultimately, such transformation successfully harmonizes Islamic legal objectives with modern human rights standards, ensuring comprehensive protection for vulnerable women and young children nationwide.